Iron-Manganese Correlation and Community Perception of Groundwater Quality - Rohmatulaeny, Wahyu Zolla; Masykuri, Mohammad; Rosariastuti, Retno; Candraningtyas, Callista Fabiola (Universitas Diponegoro, 2026)
Groundwater contamination with iron (Fe) and manganese (Mn) remains a significant challenge in rural areas with limited access to modern water treatment technologies. In the Margorejo Village, Tempel District, Sleman, groundwater from domestic wells exhibited elevated Fe and Mn concentrations related to local geochemical conditions. This study investigated the efficacy and acceptance of a hybrid phytocoagulation system combining extracts from Eichhornia crassipes and Moringa oleifera seeds to enhance metal removal through a combination of biosorption, biooxidation, and protein-induced flocculation. Variations in plant biomass (0–30 leaves), Moringa dose (0–100 mg/L), and contact time (0–16 days) were investigated in a factorial randomized block trial. The optimal configuration (30 leaves, 100 mg/L, 16 days) reduced the iron concentration to 0.082 mg/L (97.77%) and the manganese concentration to almost zero (98.71%). Pearson correlation analysis revealed a strong positive correlation between iron and manganese concentrations (r=0.821), indicating similar geochemical behavior. A public perception analysis with 30 respondents showed high acceptance (75.72%), particularly in households directly affected by contamination. These results demonstrate that hybrid phytocoagulation is a cost-effective, environmentally sustainable, and socially acceptable method for decentralized groundwater treatment and underscore the importance of public participation for long-term implementation